ОСОБЛИВОСТІ ВИКОРИСТАННЯ НАВЧАЛЬНОГО ДІАЛОГУ ПРИ ВИВЧЕННІ ІНОЗЕМНОЇ МОВИ (Педагогіка вищої та середньої школи, 2004)
The article deals with the possibilities of educational dialogue while learning the English Language by senior pupils. Special attention is paid to the usage of the educational dialogue during the lessons in home reading.